Significant Depletion of CD4+ T Cells Occurs in the Oral Mucosa during Simian Immunodeficiency Virus Infection with the Infected CD4+ T Cell Reservoir Continuing to Persist in the Oral Mucosa during Antiretroviral Therapy - Jeffy George; Wendeline Wagner; Mark G. Lewis; Joseph J. Mattapallil (Journal of Immunology Research)
Human and simian immunodeficiency virus (HIV and SIV) infections are characterized by manifestation of numerous opportunistic infections and inflammatory conditions in the oral mucosa. The loss of CD4+ T cells that play a critical role in maintaining mucosal immunity likely contributes to this process. Here we show that CD4+ T cells constitute a minor population of T cells in the oral mucosa and display a predominantly central memory phenotype mirroring other mucosal sites such as the rectal mucosa. Chronic SIV infection was associated with a near total depletion of CD4+ T cells in the oral mucosa that appear to repopulate during antiretroviral therapy (ART). Repopulating CD4+ T cells harbored a large fraction of Th17 cells suggesting that ART potentially reconstitutes oral mucosal immunity. However, a minor fraction of repopulating CD4+ T cells harbored SIV DNA suggesting that the viral reservoir continues to persist in the oral mucosa during ART. Therapeutic approaches aimed at obtaining sustainable CD4+ T cell repopulation in combination with strategies that can eradicate the latent viral reservoir in the oral mucosa are essential for better oral health and long-term outcome in HIV infected patients.